Immunohistochemical Study of Somatotrophs in Pituitary Pars Distalis of Male Viscacha (Lagostomus maximus maximus) in Relation to the Gonadal Activity - Filippa, Veronica Palmira (2007)
Somatotrophs were identified and quantified in pituitary pars distalis of male viscachas (Lagostomus maximus maximus) during the annual reproductive cycle, after the administration of melatonin, after castration and in different growth stages by immunohistochemistry and morphometric analysis. In adult male viscachas, the somatotrophs were distributed throughout the pars distalis during the reproductive cycle. They were oval, pyramidal or round in shape with a large round nucleus. The percentage immunopositive area, the major cellular diameter and the number of cells decreased during the gonadal regression period in relation to the values found in the reproductive period. The administration of melatonin did not provoke any variations of the morphometric parameters studied. On the contrary, a significant decrease in the percentage immunopositive area, in the major cellular diameter and in the number of somatotrophs in castrated viscachas was observed. The study of different growth stages showed that these morphometric parameters increased from immature to adult animals in the reproductive period. The results obtained suggested that the variations of the morphometric parameters of somatotrophs are more related to the gonadal development and activity than to a direct effect of melatonin.